Implementasi Pembelajaran Berdiferensiasi Dalam Upaya Meningkatkan Hasil Belajar Ekonomi Siswa Kelas X SMA Negeri 1 Parang Kabupaten Magetan - Nurul Hidayati; Sudarmiani Sudarmiani; Moh. Rifai (Journal on Education, 2023)
As stated in the opening of the 1945 Constitution that the goal of the Indonesian nation is to educate the life of the nation. This goal can be realized through National Education. Furthermore, Government Regulation (PP) Number 4 of 2022 concerning Amendments to PP Number 57 of 2021 concerning National Education Standards states that the competency standards of graduates in the Secondary Education Level Education Unit specifically focus on the preparation of students to become members of society who believe and fear God Almighty and have noble character. The aim of this research is to reform the implementation of differentiated learning to increase student learning activities according to each student's learning style in Economics class X 4 students at SMA Negeri 1 Parang. This type of research is Class Action Assessment (classroom action research), data collection techniques in observational research, learning achievement tests, documentation. Based on the results and discussion data, it can be concluded that the application of differentiated learning can improve the economics learning outcomes of Class X 4 SMA Negeri 1 Parang in the 2022/2023 Academic Year on the subject of Markets and Formation of Market Prices. The increase in learning outcomes is indicated by an increase in the average value of learning outcomes from cycle I to cycle II, namely in cycle I 66.78 and in cycle II 81.53. During the first cycle, there were 10 students who fulfilled the KKTP, whereas during the second cycle, there were 30 students who fulfilled the KKTP, with 75 KKTP. In the first cycle, learning outcomes increased, namely the number of students who completed 10 students (31%) while students who Not yet finished, totaling 22 students (67%) with an average value of 67. Then in cycle II there was a very high increase compared to the previous cycle, namely students who had reached KKTP totaled 30 students (94%), while students who had not completed 2 students (6%) with an average value of 82.